Epidemiology of tick-borne encephalitis in China, 2007- 2018 - Chen, Xiaojing (PLoS One, 2019)
Tick-borne encephalitis (TBE) is endemic to Europe and some Asian countries and is prevalent in northeast China. We analyzed the epidemiology of TBE in China from 2007 to 2018. A total of 3,364 TBE cases were reported in mainland China from 2007 to 2018, for an annual incidence of 0.09 to 0.44/100,000. Among the TBE cases, 89.92% were reported in forest areas (41.94% in DaXingAnLing, 8.70% in XiaoXingAnLing, and 39.21% in ChangBaiShan) in northeast China. The TBE cases were primarily male with a proportion of 67.15% (2,259/3,364 cases) and in 40–49-year age group with a proportion of 31.89% (1,073/3,364 cases). The epidemiology of TBE differed slightly among the three forest regions. Domestic workers and forestry workers accounted for the most of the TBE cases in DaXingAnLing, and domestic workers and farmers in XiaoXingAnLing and ChangBaiShan, respectively. The TBE cases mainly occurred from April to August with a peak in June. The TBE laboratory confirmed rate in DaXingAnLing (84.14%, 1,189/1,413 cases) was highest, compared with XiaoXingAnLing and ChangBaiShan (13.99% and 11.37%, respectively). Moreover, the hospital with the highest laboratory confirmed rate (88.01%, 1,336/1,518 cases) was Inner Mongolia Forestry General Hospital of DaXingAnling region. Systematic enhanced TBE surveillance and a vaccination program are needed to improve the laboratory confirmed rate and reduce the incidence of TBE in northeast China.